Secondary School Admission and Adolescent Mental Health : Evidence from a Regression Discontinuity Design - Laaksonen Jukka; Vaalavuo Maria; Dobewall Henrik (Center for Open Science, 2026)
We study the causal effect of secondary school admission on adolescents’ mental health using extensive Finnish register data and a regression discontinuity design. Focusing on two separate margins among first-time applicants in 2008–2013—admission to vocational secondary education versus no admission, and admission to general versus vocational education—we examine short- and medium-term mental health impacts measured by healthcare utilization and psychotropic drug use.
We find that admission to vocational education, relative to rejection by all applied secondary schools, reduces psychotropic drug use by 6.3 percentage points (-21%) within seven years of admission. While access to vocational education slightly increases healthcare visits in some areas, it substantially decreases visits for substance use. Moreover, we observe that admission to general rather than vocational education decreases specialized healthcare visits for mental health by 4.5 percentage points (-21%) within seven years of admission.
The effects of admission to vocational education versus no admission emerge primarily after completing vocational education, possibly related to simultaneous labor market integration. Conversely, the effects of admission to general versus vocational education mostly appear already during the immediate years after admission, potentially driven by changes in peer characteristics and living arrangements. While causal mechanisms behind the mental health effects remain unclear, our results highlight important short- and medium-term mental health benefits of secondary education. These findings point to the potential value of policies that ensure access to secondary education, such as extensions of compulsory education, and that support mental health during critical educational transitions.